Cirebon Regional Government Policy To Protect Child Victims Of Sexual Violence - Waluyadi; Marlina, Tina; Gumilang, Iwan G.; Irwany Indriyanti, Diah; Yuniarsih Genuni, Rianda (Universitas Brawijaya, 2024)
This paper examines victims from the standpoint of criminal law, as well as the Cirebon Regency government’s policy and implementation for protecting child victims of sexual violence based on a sociolegal method supported by primary and secondary data. Data collection is based on literature studies, documentary studies, and interviews. Research data were analysed based on a qualitative method. The findings of the study reveal that victim protection in criminal law is indirect. The Cirebon Regency government established regional regulations, regent regulations, and regent instructions to protect child victims of sexual violence. A non-governmental organisation in the Cirebon Regency shows concern about child victim protection since the protection of child victims of sexual violence in the Cirebon Regency has not been appropriately implemented.